INDONESIA AS NON-PERMANENT MEMBER OF UNITED NATIONS SECURITY COUNCIL, GUARDING THE PEACE AND STABILITY IN ASEAN - Afandi Sitamala (Faculty of Law Universitas Lampung, 2020)
The overall objective underlying the establishment of the UN Security Council was to “save succeeding generations from the scourge of war” (Preamble to the UN Charter) which used as the official campaign by the Indonesia Foreign Ministry, Indonesia stated itself as ‘A True Partner for World Peace’. By that, Indonesia expresses the gravity of its membership by aiming towards ascertaining collaborations between the regional organizations in maintaining stability in the regional area (ASEAN). Indonesia’s goals for bridging UNSC hegemony on the global level and bringing the stability of the ASEAN area is going to be effortful. The challenge of establishing the UN resolution as a legal instrument in municipal law becomes one of the biggest challenges. The two years of tenure also grow into a barrier toward Indonesian contributions. This study aims to analyze Indonesia role as the non-permanent member of UNSC globally and in the ASEAN Region. The final results were presented in a descriptive manner, which gives an overview of how Indonesia’s role in the UNSC, and how Indonesia’s aimed toward synergized ASEAN.